Comparative Analysis of Amino Acid Composition, Fatty Acid Profiles, and Genetic Diversity Among Three Populations of Penaeus semisulcatus - Yundong Li; Juan Chen; Ziyi Jiang; Song Jiang; Qibin Yang; Lishi Yang; Jianhua Huang; Jianzhi Shi; Yangyang Ding; Tianmi Liu; Falin Zhou (Journal of Marine Science and Engineering)
Penaeus semisulcatus, a commercially valuable aquaculture species, is widely distributed along the southeastern coast of China and throughout the South China Sea. Despite its economic importance, the comprehensive understanding of its germplasm characteristics remains limited. This investigation evaluated nutrient profiles, amino acid composition, lipid constituents, antioxidant capacity, and genomic variability across three farmed aquaculture populations maintained under standardized environmental parameters to discern divergence in nutritive attributes and hereditary characteristics. The results revealed significant interpopulation variation in ash content (p < 0.05), while other proximate components showed comparable levels. Among 17 detected amino acids, glutamic acid was the most abundant (2.07–2.30 g/100 g), while cysteine had the lowest concentration (0.10–0.11 g/100 g). Notably, the PsHK population had a relatively higher amino acid content, indicating superior nutritional value. Fatty acid analysis detected 13 fatty acids, with C18:0 (88.27–108.00 mg/100 g) being the most abundant, and C20:2 (3.40–4.70 mg/100 g) the least. The PsHK population exhibited significantly higher levels of all fatty acids compared to the other two populations (p < 0.05). Antioxidant enzyme activity assays revealed no significant differences in antioxidant capacity across the three populations, indicating a similar overall antioxidant status. Genetic diversity analysis indicated that the PsHK population had the highest genetic diversity, with a relatively pronounced genetic differentiation between the PsHK and PsRP populations. In conclusion, the comparative analysis of these three cultured populations highlights that the PsHK population excels in both nutritional composition and genetic diversity. With its superior nutritional profile and rich genetic background, P. semisulcatus shows great potential for aquaculture development. These findings provide valuable insights for future germplasm improvement and aquaculture optimization efforts, offering a scientific basis for refining breeding strategies and enhancing the nutritional evaluation of P. semisulcatus. Additionally, the comparative analysis of genetic diversity and biochemical composition contributes to a better understanding of population variation, which is essential for the sustainable management and utilization of this species in aquaculture.